Challenges of sustainable mobility: Context of car dependency, suburban areas in Thailand - Iamtrakul Pawinee; Chayphong Sararad (Geographica Pannonica, 2023)
Urbanization and transportation have caused two critical issues in the challenge of sustainable development, particularly, challenges to sustainable mobility in the context of car dependency. This is due to all aspects of environmental, social, and economic has been continued influenced by transportation related issues. The challenges of sustainable mobility in the context of suburban areas have become aggravating situation due to massive migrations, thus Pathumthani province, represented as vicinity area of Bangkok, Thailand was selected as a case study. Data were collected from 1,998 respondents by questionnaire survey and analyzed using statistical analysis and visualization based on geographic information system, GIS application. The study results revealed that the urbanization process has led to an increase in urban development that attracts enormous migrations in searching for their opportunities (working and education trips). This phenomenon has positioned Pathumthani to serve as a supportive area for the spillover of rapid urbanization in the country's capital area which has led to the development of private car-dependent travel and public transport network, mainly concentrated in urban areas with exclusion to residents in remote areas. On the other hand, most areas sprawl with a scattered density of residential settlements, which existing transportation system development can no longer serve the continued rising travel demand as before. The findings confirmed that the current development pattern could not promptly meet the needs of suburban development, requiring the policymakers to launch an effective plan to meet appropriate transportation demands and promote good quality of travelling for the residents and commuters.